1971
DOI: 10.1007/bf00149062
|View full text |Cite
|
Sign up to set email alerts
|

Motions of H?-spicules along the solar limb

Abstract: A series of Ha-spectrograms obtained with the 21 in. Lyot coronagraph has been examined. Measurements of relative distances between spicules (nearly 50 features) embrace the time interval of about 21 min (38 pictures). It is found out that spicules oscillate along the limb with a characteristic time interval (period) about 1 min, characteristic amplitude of 1 arc sec and velocities about 10-15 km/s. The oscillations show no correlation for distant spicules.As was established by numerous observators, Doppler ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 2 publications
3
20
2
2
Order By: Relevance
“…Oscillations in spicules with ∼5 min period have been detected by ground based (Kulidzanishvili & Zhugzhda 1983) and recently by space observations (De Pontieu et al 2003;Xia et al 2005). On theother-hand, oscillations in spicules with shorter period have been reported more than 30 years ago by Nikolsky & Platova (1971). They found that spicules oscillate along the limb with a characteristic period of about 1 min.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Oscillations in spicules with ∼5 min period have been detected by ground based (Kulidzanishvili & Zhugzhda 1983) and recently by space observations (De Pontieu et al 2003;Xia et al 2005). On theother-hand, oscillations in spicules with shorter period have been reported more than 30 years ago by Nikolsky & Platova (1971). They found that spicules oscillate along the limb with a characteristic period of about 1 min.…”
Section: Introductionmentioning
confidence: 90%
“…If spicules are formed in thin magnetic flux tubes, then the periodic transverse displacement of the axis observed by Nikolsky & Platova (1971) probably was due to the propagation of kink waves. It is well known that transverse kink waves can be generated in photospheric magnetic tubes by buffeting of granular motions (Roberts 1979;Hollweg 1981;Spruit 1981;Hasan & Kalkofen 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they noted a period of oscillation between 1 to 4 min, an amplitude of about 1 and a maximum lateral velocity of ∼15-25 km s −1 , very similar to the values derived in this work. Nikolsky & Platova (1971) showed that some spicules change their position along the slit, thereby showing a real horizontal component of velocity. Furthermore, they concluded that spicules can execute quasi-periodic oscillations parallel to the limb with a period of ∼1 min, an amplitude of 1 and velocities around 10-15 km s −1 , similar to the more recent work cited above.…”
Section: Possible Association With Waves -Further Justifying Flux Tubmentioning
confidence: 99%
“…The transverse displacement in spicules was initially noted by Nikolsky & Platova (1971) within solar limb observations. The authors showed that some spicules change their position along the slit, thereby showing a horizontal component of velocity.…”
Section: Introductionmentioning
confidence: 84%